The EFL Students Perception on Zoom Meeting as a Teaching Platform: A Survey Research - Deny Ferdiansah; Ogi Danika Pranata; Herayati Herayati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Education methods that were previously employed in face-to-face contacts were terminated to stop the corona virus from spreading. In higher education, e-learning has taken the place of conventional techniques as the standard. At 3 State Universities in Jambi Province, this study tries to ascertain how EFL students’ Perception about Zoom Meeting as a teaching platform. A quantitative descriptive survey was utilized. 35 students who had participated in online coursework utilizing Zoom Meeting were part of this study. Students were given surveys online in order to gather data about their perception. The majority of students are favorable about utilizing Zoom Meeting for online learning. The findings of this research suggest that: (1) Students will continue to use Zoom Meeting because it offers new learning opportunities and benefits, (2) Users can easily use Zoom Meeting’s features, (3) It is the preferred online learning platform, (4) It can help students improve their IT skills, (5) Students will continue to use Zoom Meeting when online learning, (6) Students are not finding Zoom Meeting to be seriously problematic, and (7) Students may simply complete online learning activities using Zoom Meeting.